On the Problem of Bending of Transversally Isotropic Plates - Bozhydarnyk, V. (Engineering Transactions, 2000)
The possibility of analysis of transversally isotropic plates of medium thickness by means of representing the displacements in the form of finite series along the lateral coordinate is examined. Differential equations of the twelfth order are derived. Conditions on the plate boundaries are determined. Examples of numerical calculations are presented. The article is a sequel to papers [11–13].